2020
DOI: 10.20944/preprints202011.0423.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data Types and the Phylogeny of Neoaves

Abstract: The phylogeny of Neoaves, the largest clade of extant birds, has remained unclear despite intense study. The difficulty associated with resolving the early branches in Neoaves is likely driven by the rapid radiation of this group. However, conflicts among studies may be exacerbated by the hypothesis that relationships are sensitive to the data type analyzed. For example, analyses of coding exons typically yield trees that place Strisores (nightjars and allies) sister to the remaining Neoaves, while analyses of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 59 publications
5
25
0
Order By: Relevance
“…For example, when the ∑Δln L criterion is used, VI + VII as the earliest Neoavian branch received much higher support in analyses of non-coding data, especially introns, than it did in analyses of coding data (10.9% for introns, 7.4% for UCEs, and 2% for exons). These results agree with the data type effects reported by Reddy et al (2017) and by Braun and Kimball (2021), although the differences among data types also appear to be more complex than the results suggested before.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…For example, when the ∑Δln L criterion is used, VI + VII as the earliest Neoavian branch received much higher support in analyses of non-coding data, especially introns, than it did in analyses of coding data (10.9% for introns, 7.4% for UCEs, and 2% for exons). These results agree with the data type effects reported by Reddy et al (2017) and by Braun and Kimball (2021), although the differences among data types also appear to be more complex than the results suggested before.…”
Section: Resultssupporting
confidence: 91%
“…Fundamentally, there are only two ways to examine conflict using the concatenated approach. First, one can subdivide data based on some criterion, such as coding vs. non-coding data (e.g., Jarvis et al 2014, Reddy et al 2017; Braun and Kimball 2021) or protein structure (e.g., Pandey and Braun 2020; Gordon et al 2021), and conduct concatenated tree searches on the data subsets. Second, one can examine differences in the tree selection criterion (typically the likelihood) for various topologies at the level of the genes (Shen et al 2017) or the individual site level (Kimball et al 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of different data types in that study [ 11 ] still yield limited support for the weakly supported relationships found in this study. Incomplete lineage sorting and data-type effects (the topological differences associated with the use of different types of markers [ 44 , 45 ] may have caused the instability within this clade [ 13 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Morphological data, by contrast, suggest a sister group relationship between the Caprimulgidae and the Nyctibiidae and recover both taxa as nested within Strisores (Mayr 2010). Whereas morphological data suggest that the Steatornithidae are the earliest branching taxon of the Strisores, most current molecular analyses support a sister group relationship between the Steatornithidae and Nyctibiidae (this topology is, however, sensitive to the data type analysed and is not recovered in analyses of non‐coding sequences; Braun & Kimball 2021).…”
mentioning
confidence: 77%